Multiethnic Federal State: Social and Philosophical Analysis of the Concept - N.V. Bekirov (Ученые записки Казанского университета: Серия Гуманитарные науки)
The paper deals with the problem that has been considered as poorly relevant in theoretical legal studies. The urgent drafting and adoption of the Constitution of the Russian Federation in the early 1990s to prevent disintegration of the country predetermined the utilitarian and pragmatic approach to elaboration of both essential provisions and separate articles of the document. There was no deep insight into the realities of the Russian statehood; searching was performed for the combination of categories, terminology, and certain concepts that would be acceptable for the actual subjects of the federation and allow to formally and legally preserve the state’s unity. The past clearly demonstrated the narrowness of this approach for construction of a firm legal foundation of the multiethnic federal state. The purpose of the paper is to define pressure points that were not discovered in time and healed with the constitutional legal measures. The tasks of the study are to identify the most important problems in the present state structure of Russia, as of a multiethnic federal state that developed as a result of the interaction between many nations characterized by various regional, cultural, and demographic features; to carry out meta-legal and socio-philosophical analysis of the specificity of the current national and ethnic situation in Russia with account of socio-psychological, political, and ethnocultural factors. On the basis of the obtained results, the category of democracy in multiethnic state is considered, interrelations of ethnic representation and ethnic composition of the power bodies are determined, interaction of the national and ethnic component with other components of the political and legal process are discussed. Weak spots are found in the current state structure of Russia that are the consequences of the lack of attention towards the legal status of the subjects of the Russian state, i.e., indigenous communities of Russia, underelaborated logic of the “asymmetrical” federation, psychological stereotypes preventing critical overthinking of the situation. The theoretical analysis turns out to be consonant with the interests of representatives of the civil society, who try to draw attention to the need of ensuring the actual equality of indigenous communities of Russia. The necessity to initiate wide-scale public and scientific discussion in order to project practical suggestions for the constitutional reform of Russia in the sphere of national relations is substantiated.